PENGARUH RASIO KEUANGAN TERHADAP PREDIKSI KEBANGKRUTAN (ALTMAN Z-SCORE) INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2011 - Eneng Vira Asia; Irwan Ch (Jurnal Visionida, 2015)
This study aimed to determine the effect of financial ratios to bankruptcy prediction (Altman Z-Score) food and beverage industry are listed in Bursa Efek Indonesia 2009-2011. The population in this study is a food and beverage companies listed in Indonesia Stock Exchange consists of 23 companies. Sampling of the 16 food and beverage companies conducted by purposive sampling. Analysis of the data using the model Altman Z-Score to predict bankruptcy and multiple linear regressions to determine the effect simultaneously and partially. The results showed that there were four companies that could potentially bankrupt, 3 companies with predicate gray area and 2 companies with healthy predicate and the remaining seven companies each predicate is not potentially bankrupt 1 and 2 times during the three years of research from 2009 to 2011. In this study variables Working Capital to Total Assets (WCTA), Retained Earnings (RETA), EBIT to total assets (EBTTA), Market Value of Equity to Total Liabilities (MVETL), Sales to Total Assets (STA) simultaneously significant effect on prediction bankruptcy and partially only variable Market Value of Equity to Total Liabilities (MVETL) that no significant effect on bankruptcy prediction.Keywords: financial ratios, bankruptcy prediction